Global irrigated area mapping: overview and recommendations - Droogers, Peter (International Water Management Institute, 2002)
This working paper gives an overview of the available global datasets on irrigated areas and an evaluation of their strengths and weaknesses. From these analyses an outline on how to develop a global irrigated area map, based on a generic methodology, is be presented. Some examples are given for the area covering India, Pakistan and Sri Lanka. These countries offer a broad range of irrigated areas in different environmental settings, ranging from deserts to humid tropics